PERBANDINGAN TINGKAT PARTISIPASI PEMILIH DI KABUPATEN GROBOGAN DALM PEMILUKADA KABUPATEN GROBOGAN 2011 DAN PEMILUKADA JAWA TENGAH 2013 - Adhitya Oktayudiarta Saswoyo; Puwoko .; Susilo Utomo (Journal of Politic and Government Studies, 2014)
Public participation is an indicator of the quality of democracy. One of theinstruments of democracy is elections. Direct the General Election is an attempt toencourage the participation of people who are pioneering the way towards thedevelopment of regional autonomy. The number of direct participation in the electionGrobogan from period to period are likely unstable. Grobogan regent held the firstelection in 2006, and the governor election in 2008. Voter participation rates in regentelection in 2006 and 2011 no more than 70%, while the participation rate in thegubernatorial election Grobogan from 2008 and lower in 2013 ie 50.64% and46.15%.The purpose of this study to determine differences in the level of participationon Election 2011 and Election Kab.Grobogan Central Java in 2013, also to comparethe extent of involvement of community participation in Kab.Grobogan in Election2011 and Election Kab.Grobogan Central Java in 2013 in Kab.Grobogan. The methodof approach used in this study is a survey research. The collection of primary dataobtained through a questionnaire through the study of literature as well as theprocessing and analysis of data in the form of quantitative methods.From the research, it is known that the majority of respondents have greatervoting behavior on Pilbup 2011 are 72%, whereas in 2013 only 44% pilgub. This wasdue to more direct Pilbup Grobogan concerning public welfare. Differences Pilbupvoter turnout in 2011 with Governor Election 2013 can also be seen from theproximity factor, in addition to the 47% of respondents argued Pilbup voting in 2011as a candidate interested in the figure and as much as 18% due to the advice ofreligious leaders / community.Researchers concluded that there are differences in the level of communityparticipation in the election regents and governors election. Judging from some of thevariables, namely the level of education, administrative reasons not listed in the DPT,attachment figure and pilgub pilbup candidates, as well as rural areas or districts oforigin.Keywoord : General Election, Voter Participation, Grobogan.